QbD-based Simultaneous Estimation of Chlorpheniramine Maleate, Dextromethorphan Hydrobromide and Guaifenesin in its Combined Dosage Form Using High-Performance Thin-Layer Chromatographic Method - Dedhiya, Praful P. (International Journal of Pharmaceutical & Biological Archive, 2021)
Current research work entails systematic analytical quality by design-based development of high-performance thin-layer chromatographic method for simultaneous estimation of chlorpheniramine maleate (CPM), dextromethorphan hydrobromide (DEX), and guaifenesin (GUA) in their combined dosage form. Analytical target profile was defined and critical method attributes and potential method parameters were screened by preliminary trials and scientific knowledge. Critical method parameters were identified using Taguchi OA screening design. 32 full factorial design was used for optimization of analytical method taking volume of water and migration distance as critical method parameters and by evaluating resolution between consecutive peaks of three drugs. Response surface model was validated by comparing predicted response with actual responses. Chromatographic separation was accomplished using alumina backed silica gel 60F254 as stationary phase and n-butanol-water-glacial acetic acid (7:2.5:0.5, % v/v) as mobile phase. Validation of developed method was performed as per ICH guidelines with linearity ranging between 50 and 2500 ng/band for CPM and 1000 and 5000 ng/band for DEX and GUA. Marketed syrup formulation was analyzed using developed analytical method. The results demonstrated utilization of analytical quality by design approach for screening and optimization of factors contributing development of high-performance thin-layer chromatographic method for better separation and quantification of CPM, DEX and GUA.